Exploring metacognitions in health anxiety and chronic pain: a cross-sectional survey - Rachor, Geoffrey S.; Penney, Alexander (My University, 2020)
The occurrence of health anxiety (HA) in chronic pain is associated with adverse outcomes. As such, it is important to identify constructs that might influence HA and pain-related outcomes. Metacognitions are an emerging area of interest in both HA and chronic pain, but the relationship between the three factors has not been extensively examined. The current study sought to examine the role of metacognitions about health in HA and pain-related outcomes in chronic pain.
Keywords: chronic pain; disability; health anxiety; metacognitions; metacognitions about health